Development and Implementation of Short Courses to Support the Establishment of a Prehospital System in Sub-Saharan Africa: Lessons Learned from Tanzania. (1st December 2019) - Sawe, Hendry R.; Mfinanga, Juma A.; Kisakeni, Samwel; Shao, Patrick; Nkondora, Paulina; White, Libby; Bollinger, Christina; Kulola, Irene B.; George, Upendo N.; Runyon, Michael S.; Noste, Erin
Abstract : Background . Tanzania has no formal prehospital system. The Tanzania Ministry of Health launched a formal prehospital system to address this gap. The Muhimbili University of Health and Allied Sciences (MUHAS) was tasked by the Ministry of Health to develop and implement a multicadre/provider prehospital curriculum so as to produce necessary healthcare providers to support the prehospital system. We aim to describe the process of designing and implementing the multicadre/provider prehospital short courses. The lessons learned can help inform similar initiatives in low- and middle-income countries. Methods . MUHAS collaborated with local and international Emergency Medicine and Emergency Medical Services (EMS) specialists to form the Emergency Medical Systems Team (EMST) that developed and implemented four short courses on prehospital care. The EMST used a six-step approach to develop and implement the curriculum: problem identification, general needs assessment, targeted needs assessment, goals and objectives, educational strategies, and implementation. The EMST modified current best EMS practices, protocols, and curricula to be context and resource appropriate in Tanzania. Results . We developed four prehospital short courses: Basic Ambulance Provider (BAP), Basic Ambulance Attendant (BAAT), Community First Aid (CFA), and EMS Dispatcher courses. The curriculum was vetted and approved by MUHAS, and courses were launched in November 2018. By the end of July 2019, a total of 63 BAPs, 104 BAATs, 25 EMS Dispatchers, and 287 CFAs had graduated from the programs. The main lessons learned are the importance of a practical approach to EMS development and working with the existing government cadre/provider scheme to ensure sustainability of the project; clearly defining scope of practice of EMS providers before curriculum development; and concurrent development of a multicadre/provider curriculum to better address the logistical barriers of implementation. Conclusion . We have provided an overview of the process of designing and implementing four short courses to train multiple cadres/providers of prehospital system providers in Tanzania. We believe this model of curricula development and implementation can be replicated in other countries across Africa.